PENERAPAN LKPD BERBASIS PEMBELAJARAN MENDALAM PADA SISWA KELAS V DI SD NEGERI 174/VII MERIBUNG II KABUPATEN SAROLANGUN - Karnila; MY, Mahmud; Firdaus, Heroza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of Student Worksheets (LKPD) based on Deep Learning has become an important strategy for creating meaningful, active, and student-centered learning. This study aimed to describe the implementation of Deep Learning-based LKPD for fifth-grade students at SD Negeri 174/VII Meribung II, Sarolangun Regency. This research employed a qualitative approach with a descriptive research design. The research participants consisted of the principal, fifth-grade teacher, and students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings revealed that the implementation of Deep Learning-based LKPD was carried out through three stages: introductory activities, material presentation, and practical learning activities using LKPD. The implementation enhanced students' learning engagement, critical thinking skills, collaboration, and conceptual understanding. Supporting factors included teachers' understanding of the Deep Learning approach, systematic instructional planning, and the use of contextual LKPD. Meanwhile, the main obstacles were limited instructional time, inadequate facilities, and differences in students' learning abilities. These challenges were addressed by adapting instructional strategies, utilizing the surrounding environment as a learning resource, and providing additional guidance to students who encountered learning difficulties. Therefore, Deep Learning-based LKPD can serve as an effective instructional alternative to improve the quality of science and social studies (IPAS) learning in elementary schools.